Hotel Resort di Kawasan Wisata Waduk Jatiluhur Kabupaten Purwakarta Jawa Barat - Galih Prasetyo; Rina Widiyanti; Lia Rosmala Schiffer (Jurnal Arsitektur Wastu Padma, 2024)
The purpose of architectural criticism on the Jatiluhur Reservoir is to describe and emphasize a descriptive criticism that exists on the Jatiluhur Reservoir. The Jatiluhur Reservoir is located. Purwakarta Regency is part of the territory of West Java Province, which is situated between 107°30'–107°40' East Longitude and 6°25'–6°45' South Latitude, with an area of 971.72 Km2 or about 2.81 per cent of the area of West Java Province. The Purwakarta Reservoir has vast potential in West Java; development includes hotels, mosques, shopping area arrangements, camping, and parking lots.